Exploring the Impact of Drug Use History and Abuse on Crime Propensity and Behavior among Inmates in Nigerian Correctional Facilities - Abayomi O, Olaseni (Journal of Ecohumanism, 2025)
This study examined the influence of drug use histories on crime propensity among 450 convicted inmates (M = 36.7, SD = 0.7) using an ex post facto design and purposive sampling. Data were collected through the drug use history and the Crime and Criminal Behavior Checklist. Results showed that drug use history significantly influences crime propensity and behavior among convicted inmates in Kwara State [F(2,375) = 11.44, p < 0.01]. The eta squared (η2) coefficient revealed that 76% (ηp2=0.76) of the variance in crime propensity and behavior among participants. The Scheffé post-hoc analysis results indicate that respondents with a history of drug addiction exhibited the highest crime propensity and behavior (= 24.39; SD = 02.39), compared to those with a history of drug use (= 21.45; SD = 08.51) and those with no history of drug use (=18.94; SD = 03.12). . The study highlights the need for trained psychologists in correctional facilities to provide targeted interventions. Given its focus on convicted inmates, further research is recommended to explore broader populations on drug use, and additional psychological factors influencing criminal behavior.